1989
DOI: 10.1177/000331978904000307
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Evidence of an Adenosine-Mediated Mechanism of Calcium Entry Blocker Activities

Abstract: Drugs such as dipyridamole (200 micrograms/kg/min), an adenosine uptake inhibitor, and theophylline (300 micrograms/kg/min), an adenosine receptor antagonist, respectively increased and decreased postischemic hyperemia in normal subjects, as well as in POAD patients. Moreover, dipyridamole pretreatment was able to antagonize the reduction of peak flow induced by nifedipine, and the potentiating effect of flunarizine on postischemic hyperemia was affected significantly by theophylline, thus suggesting a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…and of myocytes.Pv'" The biologic significance of extracellular adenosine increase is related to its local vasodilating and tissue-protecting properties during ischaemia and inflammatory reactions. 24,25,36,37,41,42 Moreover, adenosine regenerates the intracelIular adenine nucleotide pool after membrane uptake.P Restoration of intracellular ATP content helps preservation of cell viability during ischaemia and reperfusion. ":" ATP also contributes to endothelium-dependent vasodilation during ischaemic events."…”
Section: Discussionmentioning
confidence: 99%
“…and of myocytes.Pv'" The biologic significance of extracellular adenosine increase is related to its local vasodilating and tissue-protecting properties during ischaemia and inflammatory reactions. 24,25,36,37,41,42 Moreover, adenosine regenerates the intracelIular adenine nucleotide pool after membrane uptake.P Restoration of intracellular ATP content helps preservation of cell viability during ischaemia and reperfusion. ":" ATP also contributes to endothelium-dependent vasodilation during ischaemic events."…”
Section: Discussionmentioning
confidence: 99%
“…The ADO increase may be of pharmacological interest since following CsA and FK506 administration, ADO reaches values high enough to be of physiological relevance [36,37]. The biological significance of extracellular ADO increase is related to its vasodilating and tissue protecting properties during ischaemia and inflammatory reactions [36–43], mediated by the interaction with four specific membrane receptors, termed A1, A2A, A2B and A3 [18,44,45]. Moreover, ADO is also provided with natural immunosuppressive activities including inhibition of cytokine release, namely tumor necrosis factor (TNF)‐ α , interleukin (IL)‐2 and IL‐6 [14,15,17,18,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we further demonstrated that, in the presence of adenosine, an ATP-induced [Ca 2+ ]i response was observed in arteriole smooth muscle cells -although this reaction was partially inhibited. Because adenosine A1 receptors mediate the inhibition of L-type Ca 2+ channels (Di Perri et al, 1989;Rocher et al, 1999), the effects of dipyridamole on resistance vessels may be partly explained by the potentiation of adenosine mechanisms rather than the potentiation of NO or other cGMP-mediated actions (Gamboa et al, 2005).…”
Section: Response Of Smooth Muscle Cells In Testicular Arterioles Witmentioning
confidence: 99%